Towards a Contract Basis of Valuation in Accounting. - Hughes, John S. (The Accounting Review, 1978)
ABSTRACT: This article provides a rigorous development of a contract (or commitment) basis of accounting as an alternative to the exchange basis in present use. Specifically, the analysis deals with the valuation of executory contracts including purchase commitments, forward contracts in foreign exchange, employee stock options, and leases. Notwithstanding the severity of assumptions, the analysis provides a coherent, logical, and widely applicable model of valuation in accounting.